Peningkatan Pengetahuan Ibu dalam Pemanfaatan Buku KIA terhadap Deteksi Dini Tumbuh Kembang Anak Usia Dini - Revinel Revinel; Dina Sulviana Damayanti; Aning Subiyatin (Universitas Pahlawan Tuanku Tambusai, 2026)
A very important period to attention for a child's growth and development so that any abnormalities in their growth and development can be detected as early as possible is the age of 0 to 5 years, this period is often also called the